The identity and social mobility of Sama-Bajau - Gusni Saat, (Universiti Kebangsaan Malaysia, 2003)
This brief article deals with identity consolidation and its impact on the social mobility of Sama-Bajau in Malaysia, the Philippines and Indonesia. It interprets how identity consolidation among Sama-Bajau has improved their social status. There were three basic components of identity among Sama- Bajau throughout the Malay World during the colonial period: namely the common terms of reference, Sama or Bajau, their language and their religion, Islam. These were closely associated with their being boat people, being relatively un-Islamic, and having a maritime economic base. These characteristics were an embarrassment in the eyes of dominant neighbouring groups, and earned Sama-Bajau a low social status. The ability of Sama-Bajau to raise social status was strongly connected to the dynamic process of identity consolidation. Their history throughout the region implies that when their social status was raised, it was due to a transformation of those three elements of identity, a development which was strongly influenced by both structural and cultural factors